Hubungan antara Budaya Organisasi dengan Kepuasan Kerja Guru Honorer SD Negeri di Kecamatan Pulogadung Jakarta Timur - Siti Annisa; Neti Karnati; Heru Santosa (Improvement: Jurnal Ilmiah untuk Peningkatan Mutu Manajemen Pendidikan, 2017)
This research aims to determine the relationship between organizational cultureand job satisfaction of honorary teacher Elementary School in district Pulogadung EastJakarta. This research is quantitative with two variables, namely: (X) Organizationalculture as the independent variable and (Y) job satisfaction as the dependent variable.The research method used is survey method with the correlational studies andquantitative approaches. Samples were as many as 73 honorary teachers. Samplingtechnique using simple random sampling by the formula Slovin and data collection usingquestionnaires. From the results of hypothesis testing, obtained tcount = 6.38, which meansbigger than ttable = 1.9939. Thus it can be said that the hypothesis can be received. Itmeans null hypothesis (Ho) is rejected. Organizational culture contributed 36.46% to thejob satisfaction of honorary teacher Elementary School in District Pulogadung EastJakarta. Based on the results of the research note that the increasingly strongorganizational culture, then the higher job satisfaction of honorary teacher ElementarySchool in District Pulogadung in East Jakarta. It can be concluded that there is a positiverelationship between organizational culture and job satisfaction of honorary teacherElementary School in district Pulogadung East Jakarta.